The City Speaks. Exile, Consolation, and Drama in the Book of Baruch - Wilson, Walter T. (Biblische Zeitschrift, 2026)
Scholarship on the song of Baruch (4,5-5,9) has focused largely on the author’s interactions with texts culled from scripture (especially Second and Third Isaiah) and how its modes of intertextuality differ from those discerned in other parts of the book. This study expands upon such work by examining the song as a drama, attending to issues such as plot, setting, dialogue, and spectatorship, the lead actor being personified Jerusalem, who assumes the roles of mother, mourner, supplicant, consoler, and - not least of all - prophet. This approach invites comparison with similar dramatic performances, including the Sumerian city-laments, which (like the book of Baruch) appear to have been created for liturgical use.